Perception of lecturers and students on entrepreneurship education on venture creation: the case of Gweru Polytechnic College, Zimbabwe - MABHANDA, WILSON (IJRDO - Journal of Applied Management Science, 2016)
Entrepreneurship education has emerged as an instrument for poverty alleviation, by way ofproviding opportunities and avenues of career options and choices even to graduates ofpolytechnic education. The purpose of this study is to explore the perception of studentstowards entrepreneurship education in influencing venture creation after their tertiaryeducation. The researcher employed a case study method approach where data was collectedthrough focus group discussions, open-ended questionnaires and face to face interviews.Purposive sampling was employed to collect data for this study. Data were thematicallyanalysed in line with the qualitative research approaches. It emerged from empirical findingsof this study that both lecturers and students share similar views that Entrepreneurship SkillsDevelopment (ESD) is a welcome additional curriculum because it has the potential to booststudents’ motivation to create their own ventures after school. The study findings highlightedinadequate content, lack of depth, less time allocated for the subject and otherwise lecturerswho teach it are very qualified but not in entrepreneurship as a discipline. This studyrecommends that ESD curriculum be enriched and students be given option to take up as adiscipline to Higher National Diploma in Entrepreneurship. Furthermore, expert lecturersare to be recruited to teach entrepreneurship education in polytechnic colleges in Zimbabwe.The government of Zimbabwe must take a robust intervention to assist new venture creationacross the country in order to mitigate poverty by employing home grown solutions sustainedby Zimbabwe Agenda for Sustainable Socio- Economic Transformation ( ZIMASSET).